Root Canal Irrigation NaOCl plus Nano Chitosan as an Antibacterial Pseudomonas Aeruginosa - Dewa Made Wedagama (Indonesian Dental Association, 2025)
Chitosan tilapia scales is one of the chitosans which has benefits as an antibacterial in dental root canal, the physical size of chitosan can be converted into smaller particle sizes in the form of nanoparticles. For the material of root canal irrigation as a gold standard is sodium hypochlorite 0.5% -5.25%. One of the bacteria found in the root canal is Pseudomonas aeruginosa. The purpose of this study was to determine the effectiveness of nano chitosan tilapia scales plus 1.5% and 2.5% NaOCl in inhibiting Pseudomonas aeruginosa. This research is a laboratory experimental study with the research design used is the Post Test Only Control Group Design antibacterial test Kirby Bauer. The sample used was the bacterium Pseudomonas aeruginosa which was divided into 4 groups: group 1 was the treatment group given nano chitosan of tilapia scales plus 1.5% NaOCl, group 2 was the treatment group given nano chitosan of tilapia scales plus 2.5% NaOCl, group 3 of the treatment group was given a positive control with Chlorhexidine and group 4 of the treatment group was given a negative control of aquadest with 6 repetitions for each. The results of statistical tests using the Least Significant Difference (LSD) test showed that there were significant differences in the inhibition zone between nano chitosan of tilapia scale plus 1.5% and 2.5% NaOCl with a value of r <0.05. The average inhibition power of nano chitosan of tilapia scales plus 1.5% NaOCl was 21.33 mm and nano chitosan of tilapia scales plus 2.5% NaOCl was 24.83. It can be concluded that nano chitosan of tilapia scale plus 1.5% NaOCl and nano chitosan of tilapia scale plus 2.5% NaOCl have very strong inhibition against Pseudomonas aeruginosa. Nano chitosan of tilapia scales plus 2.5% NaOCl is more effective in inhibiting Pseudomonas aeruginosa. Keywords: Root canal irrigation NaOCl 2.5%, Nano Chitosan, Antibacterial